Behavioral fragmentation in the D1CT‐7 mouse model of Tourette's syndrome. (3rd January 2018) - Santangelo, Andrea; Bortolato, Marco; Mosher, Laura J.; Crescimanno, Giuseppe; Di Giovanni, Giuseppe; Cassioli, Emanuele; Ricca, Valdo; Casarrubea, Maurizio
Summary: Aim: The transgenic D1CT‐7 mouse is one of the best‐characterized animal models of Tourette's syndrome (TS), exhibiting spontaneous tic‐like Head‐Body Twitches (HBT) and deficits in sensorimotor gating. This study is aimed at evaluating the behavioral dynamics of these mutants and their potential relevance to TS. Methods: The behavior of D1CT‐7 and Wild Type littermates was firstly assessed by considering frequencies and durations. To detect recurrent real‐time behavioral sequences, the multivariate T‐pattern analysis was employed. Analyses of transition probabilities among behaviors further provided an overall picture of the behavioral dynamics. Results: T‐patterns and transition matrices revealed in D1CT‐7 mice a clear‐cut hyperactivity compared to controls, with a lower behavioral organization and a marked shift from cautious sniffing toward locomotion. Moreover, the behavioral patterns of the transgenic mice were pervasively disturbed by intrusive tic‐like HBT leading to a marked fragmentation of the behavior. Novel exposure to open field provoked a transient inhibitory control over the disrupting phenotype. Conclusion: The results of this study show that the D1CT‐7 mouse model is subjected to a behavioral fragmentation, with repercussions going beyond the simple tic‐like phenomenon. These phenotypes are strikingly akin to behavioral problems observed in patients with TS and further validate the power of this model in summarizing pivotal behavioral aspects of TS.